New links between auxin and starch - John J. Ross; Erin L. McAdam (Nature Communications)
Auxin was one of the first plant hormones to be identified, but we are still discovering the roles of this “master” hormone. Here we discuss new evidence that links auxin with the synthesis and accumulation of one of humanity’s staple food ingredients, starch.